Revenge and forgiveness: Two sides of the same coin? - Moura, Darlene Pinho Fernandes de (2020)
The desire to punish someone who has caused suffering is characterized by revenge. However, it ispossible for someone to present pro-social changes in relation to the offender, which constitutesforgiveness. Studies point out that forgiveness and revenge can be understood in the opposite wayand also share a common dimension. In this sense, this study aimed to compare the adjustment of atwo-factor model for forgiveness and revenge with alternative explanations of one-factor and twofactormodels. 195 people participated, the majority female (66.7%), heterosexual (83.2%), single (80.8%), with incomplete higher education (68.4%) and with ages between 18 and 82 years (M=27.26; SD=11.50), who responded to the Willingness to Forgive Scale and the Vengeance Scale. The results showed that the two-factor model was more appropriate [χ2(102)=175.639, p<0.001; χ2/gl=1.54, SRMR=0.06, CFI=0.94, RMSEA=0.061 (CI90%=0.04-0.07), TLI=0.93]. The results found suggest that, in addition to sharing a common factor, the variables seem to have legitimacy as distinct constructs, providing empirical support for the promotion of strategies aimed at intervening in both general and specific elements related to the constructs.